Branched Chondroitin Sulfate Oligosaccharides Derived from the Sea Cucumber Acaudina molpadioides Stimulate Neurite Outgrowth - Weili Wang; Hui Mao; Sujuan Li; Longlong Zhang; Lian Yang; Ronghua Yin; Jinhua Zhao (Marine Drugs, 2022)
Fucosylated chondroitin sulfate (FCS) from the sea cucumber Acaudina molpadioides (FCSAm) is the first one that was reported to be branched by disaccharide GalNAc-(α1,2)-Fuc3S4S (15%) and sulfated Fuc (85%). Here, four size-homogenous fractions, and seven oligosaccharides, were separated from its β-eliminative depolymerized products. Detailed NMR spectroscopic and MS analyses revealed the oligomers as hexa-, hepta-, octa-, and nonasaccharide, which further confirmed the precise structure of native FCSAm: it was composed of the CS-E-like backbone with a full content of sulfation at O-4 and O-6 of GalNAc in the disaccharide repeating unit, and the branches consisting of sulfated fucose (Fuc4S and Fuc2S4S) and heterodisaccharide [GalNAc-(α1,2)-Fuc3S4S]. Pharmacologically, FCSAm and its depolymerized derivatives, including fractions and oligosaccharides, showed potent neurite outgrowth-promoting activity in a chain length-dependent manner. A comparison of analyses among oligosaccharides revealed that the sulfate pattern of the Fuc branches, instead of the heterodisaccharide, could affect the promotion intensity. Fuc2S4S and the saccharide length endowed the neurite outgrowth stimulation activity most.